Macrophage Migration Is Impaired within Candida albicans Biofilms - Maria F. Alonso; Neil A. R. Gow; Lars P. Erwig; Judith M. Bain (Journal of Fungi, 2017)
Candida albicans is an opportunistic fungal pathogen that infects immunocompromised patients. Infection control requires phagocytosis by innate immune cells, including macrophages. Migration towards, and subsequent recognition of, C. albicans fungal cell wall components by macrophages is critical for phagocytosis. Using live-cell imaging of phagocytosis, the macrophage cell line J774.1 showed enhanced movement in response to C. albicans cell wall mutants, particularly during the first 30 min, irrespective of the infection ratio. However, phagocyte migration was reduced up to 2-fold within a C. albicans biofilm compared to planktonic fungal cells. Biofilms formed from C. albicans glycosylation mutant cells also inhibited macrophage migration to a similar extent as wildtype Candida biofilms, suggesting that the physical structure of the biofilm, rather than polysaccharide matrix composition, may hamper phagocyte migration. These data illustrate differential macrophage migratory capacities, dependent upon the form of C. albicans encountered. Impaired migration of macrophages within a C. albicans biofilm may contribute to the recalcitrant nature of clinical infections in which biofilm formation occurs.